5
$\begingroup$

Two real sequences $(x_n)$ and $(y_n)$ are defined by $$x_{n+1}=x_n-(x_ny_n+x_{n+1}y_{n+1}-2)(y_n+y_{n+1})$$ $$y_{n+1}=y_n-(x_ny_n+x_{n+1}y_{n+1}-2)(x_n+x_{n+1})$$ with $x_0=1$ and $y_0=2007.$ I need to show that $|x_n|\lt \sqrt{2007}$ for all $n\in\mathbb{N}.$
I proved that $$x_{n+1}^2-x_n^2=y_{n+1}^2-y_n^2\,\,\,\,\,\,\,\,\,\,\forall n\in\mathbb{N},$$ which implies $|x_n|\lt|y_n|$ and $$x_n^2=y_n^2-2007^2+1.$$

Also I would like to know that, Is $x_n$ convergent? Any Idea?

$\endgroup$
  • $\begingroup$ $$x_1=-0.99900323990439297512...\approx-1$$ and $$y_1=2006.9999995036057148...\approx 2007.$$ $\endgroup$ – Bumblebee Jun 11 '15 at 5:10
  • 1
    $\begingroup$ where from with problem? and why this result is hold? $\endgroup$ – math110 Jun 11 '15 at 5:27
  • $\begingroup$ One of my friend gave me this problem. Most probably it can be some past contest problem. $\endgroup$ – Bumblebee Jun 11 '15 at 5:30
  • 1
    $\begingroup$ you can also have $$(x_{n}y_{n+1}-x_{n+1}y_{n})=(x_{n}y_{n}+x_{n+1}y_{n+1}-2)(y_{n}y_{n+1}-x_{n} x_{n+1})$$,then maybe use AM-GM inequality $\endgroup$ – math110 Jun 11 '15 at 6:50
  • $\begingroup$ It should be $$(x_{n}y_{n+1}-x_{n+1}y_{n})=(x_{n}y_{n}+x_{n+1}y_{n+1}-2)(y_n^2+y_{n}y_{n+1}-x_n^2-x_{n} x_{n+1}).$$ Is n't it? $\endgroup$ – Bumblebee Jun 11 '15 at 6:59
0
$\begingroup$

Some idea:

let $A=x_{n}y_{n}+x_{n+1}y_{n+1}-2$,since $(2)^2-(1)^2$ then we have $$y^2_{n+1}-x^2_{n+1}=y^2_{n}-2Ay_{n}(x_{n+1}+x_{n})+A^2(x_{n}+x_{n+1})^2-x^2_{n}+2(y_{n}+y_{n+1})x_{n}A-A^2(y_{n}+y_{n+1})^2$$ since $$y^2_{n+1}-x^2_{n+1}=y^2_{n}-x^2_{n}$$then we have $$A(y_{n}y_{n+1}-x_{n}x_{n+1})=y_{n+1}x_{n}-x_{n+1}y_{n}$$ or $$y_{n+1}x_{n}-x_{n+1}y_{n}=(x_{n}y_{n}+x_{n+1}y_{n+1}-2)(y_{n}y_{n+1}-x_{n}x_{n+1})\tag{2}$$

as your comment $$(2)x_{n}:y_{n+1}x_{n}=x_{n}y_{n}-A(x_{n}+x_{n+1})x_{n}\tag{3}$$ $$(1)y_{n}:x_{n+1}y_{n}=x_{n}y_{n}-A(y_{n}+y_{n+1})y_{n}\tag{4}$$ so $(3)-(4)$ $$x_{n}y_{n+1}-x_{n+1}y_{n}=A[y^2_{n}-x^2_{n}+y_{n}y_{n+1}-x_{n}x_{n+1})\tag{6}$$ for $(2),(6)$ you can have ?

$\endgroup$
  • $\begingroup$ Consider $(2)x_n-(1)y_n,$ it give a different result. $\endgroup$ – Bumblebee Jun 11 '15 at 7:59
  • $\begingroup$ if you not wrong, note $y_{n}\neq x_{n}$, then $y_{n}y_{n+1}-x_{n}x_{n+1}=0$ and $y_{n+1}x_{n}=x_{n+1}y_{n}?$ $\endgroup$ – math110 Jun 11 '15 at 8:33
  • $\begingroup$ I beg your pardon. As I can see, In your second line, there is a wrong with $(y_n+y_{n+1})^2$ and $(x_n+x_{n+1})^2.$ $\endgroup$ – Bumblebee Jun 11 '15 at 8:39
  • $\begingroup$ Oh,Now I have edit it $\endgroup$ – math110 Jun 11 '15 at 8:49
  • $\begingroup$ If both statements were true, then we have that $y_n^2-x_n^2=0.$ $\endgroup$ – Bumblebee Jun 12 '15 at 3:49

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.